PENGUJIAN TRADE-OFF THEORY: APAKAH PERUSAHAAN DI INDONESIA MELAKUKAN OPTIMALISASI HUTANG? - Fuady, Misbach (PRESTASI, 2013)
ABSTRACTÂ This study examined the role of trade-off theory (TOT) in determining the capital structure of public companies in Indonesia. Tests using data on the financial statements of public companies in Indonesia, using the model of partial adjustment targets in the period 2002 to 2011. Research carried out shows that the adjustment of the actual debt towards a target debt at a rate of 42.61% per year. It shows that public companies in Indonesia shows the optimizing behavior of debt by adjusting the actual debt towards optimal debt targets in accordance with the concept of dynamic capital structure based on the trade-off theory. Â Keyword: trade-off theory, pecking order theory, optimal capital structure